IMPLEMENTASI SISTEM PERTANGGUNGJAWABAN PIDANA KORPORASI PELAKU TINDAK PIDANA PERTAMBANGAN (Studi Putusan Nomor : 190/Pid.Sus/2016 /PN.Pmn dan Putusan No. 90/PID.SUS/2017/PT.PDG) - Wibisono, Gunawan; Fitriati, Fitriati; Ferdi, Ferdi (Program Magister Ilmu Hukum Universitas Ekasakti, 2019)
Article 46 of Law Number 32 Year 2009 concerning the Management of Environmental Protection stipulates that a Criminal Account shall be liable to any person of the Legal Entity and / or its Management. Criminal proceedings that have been broken off at the Padang Pariaman District Court where the criminal responsibility is by the corporate management. The problem is the consideration of the judge in the decision of the Mining crime committed by the corporation and the implementation of the corporation accountability system against environmental damage that occurred in the mineral mining area in Padang Pariaman Regency, West Sumatera Province. Research specification is analytical descriptive with Normative juridical approach. The data obtained were analyzed qualitatively. The results of the first study and discussion, Judge's Consideration in Decision Number 190 / Pid.Sus / 2016 / PN.Pmn and Decision No. 90 / PID.SUS / 2017/ PT.PDG the defendant fulfilled the element as the subject of criminal law of the deeds he committed. Defendant as the board (Director) of the corporation. Board is considered as a form of corporation. Second, corporate criminal liability in Decision Number 190 / Pid.Sus / 2016 / PN.Pmn and Decision No. 90 / PID.SUS / 2017 / PT.PDG sentenced to criminal is his company represented by the director of the company. Corporal criminal liability can be demanded through the doctrine of superior responders or vicarious liability.